2021
DOI: 10.3390/molecules26185491
|View full text |Cite
|
Sign up to set email alerts
|

The Phenolic Compounds Profile and Cosmeceutical Significance of Two Kazakh Species of Onions: Alliumgalanthum and A. turkestanicum

Abstract: Numerous species of Allium genus have been used in the traditional medicine based on their vast biological effects, e.g., antimicrobial, digestion stimulant, anti-sclerotic, soothing, antiradical or wound healing properties. In this work, unpolar and polar extracts from two lesser-investigated species of Allium growing in Kazakhstan, Allium galanthum Kar. & Kir. (AG) and A. turkestanicum Regel. (AT), were studied for their composition and biological effects. In the HPLC-ESI-QTOF-MS/MS analyses of water and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Phenolic compounds derived from a variety of vegetable species, including those commonly used in traditional medicine and present in foods such as fruits and vegetables, have been reported to have a positive impact on tissue regeneration [70][71][72][73][74][75][76][77][78]. Thus, Addis et al found that treatment with polyphenols extracted from medicinal plants (Calendula Arvensis, Lavandula stoechas, and Helichrysum italicum) at a concentration of 1 μL/mL increased fibroblast cell proliferation after 24 h of treatment and stimulated cell migration after 48 h, when complete closure was observed [79].…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic compounds derived from a variety of vegetable species, including those commonly used in traditional medicine and present in foods such as fruits and vegetables, have been reported to have a positive impact on tissue regeneration [70][71][72][73][74][75][76][77][78]. Thus, Addis et al found that treatment with polyphenols extracted from medicinal plants (Calendula Arvensis, Lavandula stoechas, and Helichrysum italicum) at a concentration of 1 μL/mL increased fibroblast cell proliferation after 24 h of treatment and stimulated cell migration after 48 h, when complete closure was observed [79].…”
Section: Discussionmentioning
confidence: 99%
“…The high absorbance, between 200-400 nm, makes it a natural choice for sunscreen and protection treatments, alongside TiO 2 [11][12][13]. As a semiconductor, due to its transparent coccus aureus, Bacillus cereus, Bacillus subtilis, and Enterococcus faecalis, which are responsible for many implants' failure [75,76], skin infections [77], or foodborne illnesses [78], and a fungal strain Candida albicans, responsible for oral and vaginal candidiasis [79][80][81].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the spontaneous flora of Kazakhstan, consisting of many endemic and rare species [ 20 , 21 ], can be regarded as a rich source of several, not fully explored medicinal plants with novel potential applications [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Therefore, attempts have been made to introduce them for cultivation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%